PENGARUH PENGEMBANGAN KAWASAN WISATA TERHADAP NILAI PASAR TANAH DI PULAU BALI - , WIBIANTORO DAYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this study is to analyze the impact of tourism on lands values in Bali. Particularly, it intends to analyze the impact of location, room supply, room occupation and facilities on lands values. The samples had been taken from three major tourism regents in Bali: Kuta, Nusa Dua and Sanur. The regents under investigation are tourism areas which are developed more than two decades. Multiple regression analysis has been used in this study. It is found that the various access measures have different and significant effects on land values. The lands values have been impacted by lands location and accessibility is the basic reason of this variable. Basic indicator of tourism industry, such as room supply, room occupation and facilities, also bring impact on lands value as well. The lands which are located in the area that have higher rate of room supply and room occupation have higher Market Value. Lands, with better facilities, have higher value than those with fewer facilities. The multiple regression analysis is confirmed